The Integration of Islamic Values in English Language Teaching Context: Practices and Challenges - Safitri, Citra Dwi; Jabu, Baso; Samtidar, Samtidar (Har Press Indonesia, 2023)
Studies on the integration of moral, cultural, and religious values in the non-religion subject have been greatly raised in these recent years. This research aims to find out the teachers’ strategy and challenges encountered in integrating Islamic values in English language teaching. The descriptive method with a qualitative approach is employed in this research. The subject of this research consists of three English teachers who teach in different grades from seventh to ninth at SMP Pesantren Modern IMMIM Putra Makassar. The data of this research are obtained from the observation sheet and interview guide. The data analysis technique in this research uses three steps, namely identification, classification, and explanation. The result of this research shows that there are four strategies employed by English teachers in integrating Islamic values in ELT. First, the teachers give direct advice to the students. Second, the teachers associate the lesson topic with pertinent Islamic teaching by quoting verses from the Qur’an and/or Hadith. Third, the teachers get the students used to worship through the habituation of religious activities. Fourth, the teachers refer to someone, or themselves to introduce some Islamic values to the students. The teachers also encounter several challenges in integrating Islamic values in ELT. First, the limited availability of English textbooks integrated to Islamic values. Second, the teachers have limited knowledge of how to optimally integrate Islamic values into the teaching and learning process. Third, the teachers have a limited time to provide and prepare the English learning materials associated to Islamic values. Further studies such as research and development of English textbooks that integrated to Islamic values for high school students are expected to be conducted in an attempt to solve the teachers’ challenges revealed in this research.